Microlayer enrichment in natural treatment systems: linking the surface microlayer to urban water quality. (11th December 2015) - Rippy, Megan A.; Weiden, Laura M.; Cooper, William J.; Deletic, Ana; Grant, Stanley B.
Abstract : Natural treatment systems (NTS), such as constructed wetlands and stormwater ponds, are multibenefit, multidisciplinary approaches to sustaining water resources and reducing contaminant loading to urban streams. Surficial thin films (called surface microlayers) are not well characterized in NTS, but may have important implications for ecosystems, public health, and pollutant fate and transport. We present results from a case study evaluating microlayer contaminant partitioning across 4 NTS in Melbourne, Australia. To our knowledge, this study provides the first direct evidence for microlayer formation and contaminant enrichment (total petroleum hydrocarbons and trihalomethanes) in NTS. Contaminated microlayers were detected in the three most stable NTS, with stability defined relative to wind speed. Fluorescent‐dissolved organic matter profiles differed between microlayer and subsurface water in these systems, suggesting that fluorescence‐based techniques are useful for microlayer detection. Although individual fluorophores were not consistently associated with specific contaminants, fluorescence ratios were useful for identifying likely contaminant source waters, including road‐runoff and irrigation water from nearby green spaces. We evaluate our case study in light of what is known about surface microlayers in analogous systems (e.g., oceans, estuaries, and lakes), in order to identify existing research gaps and future opportunities. WIREs Water 2016, 3:269–281. doi: 10.1002/wat2.1128 This article is categorized under: Engineering Water > Sustainable Engineering of Water Engineering Water > Water, Health, and Sanitation Science of Water > Water Quality